Problems and Countermeasures of China's Treasury Cash Management - Hua, Shi (Archives of Business Research, 2020)
This paper reviews the development process and present situation of China's treasury cash management, points out the existing problems of China's treasury cash management, analyzes the causes of these problems and puts forward corresponding solutions.